Eosinophilic solid and cystic renal cell carcinoma: a case study of the youngest surgical patient - Zhenfang Qin; Geng Li; Wen Zhang; Fang Yu; Heyun Gao; Shanzhen Yu; Guowei Du; Tao Hu; Yunkai Guo; Yifan Liu; Mingshuang Luo (Discover Oncology)
Abstract Background Eosinophilic solid and cystic renal cell carcinoma (ESC RCC) is a rare subtype of renal cell carcinoma. The tumor often presents without specific clinical symptoms or detectable signs for a definitive diagnosis. The vast majority of ESC RCC are sporadic, with a few associated with tuberous sclerosis. This case report details a young patient diagnosed with ESC RCC. We recommend complete excision of the tumor after a comprehensive evaluation, followed by postoperative pathology, to achieve a conclusive diagnosis. Case summary An 8-year-old boy was incidentally found to have multifocal renal masses in the right kidney during routine physical examination one year ago, without presenting abdominal pain or hematuria. Contrast-enhanced abdominal computed tomography (CT) revealed two isodense masses (27 × 21 mm and 20 × 16 mm) at the upper pole of the right kidney. PET imaging showed no signs of metastasis. The patient underwent robot-assisted partial nephrectomy, and postoperative pathological examination diagnosed ESC RCC. Genetic testing showed no significant abnormalities. After 8 months of follow-up, there were no signs of recurrence or metastasis. This ESC RCC case is likely the youngest case reported to date in urological oncology records, according to current data. Conclusion A combination of imaging studies and postoperative pathological examination is crucial for the definitive diagnosis of rare tumors. For small renal tumors with well-defined borders, no evidence of metastasis, and no tumor thrombus, robot-assisted laparoscopic partial nephrectomy is a viable treatment option for pediatric renal tumors. The pathogenesis of ESC RCC requires further investigation with more data.